Qard Al-Hassan model as an institutionalised method of Islamic finance - Kazak, Hasan; Alim, Hasan Basri (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to show that it is possible to apply Qard Al-Hassan (interest-free loan) within a corporate structure, enabling extra earnings rather than a decrease in money for businesses. It is obvious that this model can create a considerable solution for financial problems if it is fully understood and disseminated. As an effective solution, it aids businesses having Islamic concerns and sensitivity to stay away from interest. The purpose of this research is to propose that Qard Al-Hassan, a significant part of interest-free financial system, should become active again as it leads the businesses to increased value rather than financial losses. This study is based on a theoretical and conceptual framework and reveals a basic model in which an institutional Qard fund is established. This research considers a simple model in the form of a corporate Qard fund to show that Qard Al-Hassan will bring about overall financial benefits rather than losses. Further studies on this topic are likely to show improved and detailed versions of Qard fund. Researchers carrying out such studies on this topic will contribute to the financial world and literature. It has been pointed out that a Qard Al-Hassan fund would allow corporations to meet their financial needs, and the money corporations invest in this fund would not result in any kind of loss for them; rather, it would bring more benefits than estimated.